(untitled) (Journal of the College of Basic Education, 2025)
The research aims to find out “building an educational program based on the art of doodles to develop the skills of students of the Institute of Fine Arts in the subject of design techniques.” In order to achieve the goal of the research, the researcher formulated the following two hypotheses: -1 There are no statistically significant differences at the significance level (0.05) between the average scores of the students of the experimental group and the control group in the pre-cognitive test. -2There are no statistically significant differences at the significance level (0.05) between the average scores of the students of the experimental group and the control group in the post-cognitive achievement test. -3There are no statistically significant differences at the significance level (0.05) between the average scores of the students of the experimental group and the control group in the pre-skills test. -4There are no statistically significant differences at the significance level (0.05) between the average scores of the students in the experimental group and the control group in the post-cognitive test. To verify the validity of the hypotheses, the researcher conducted the experiment starting from 2/27/2024 until 3/14/2024. The research community consisted of students from the Institute of Fine Arts, and the research sample was chosen from the students of the Design Department - third year - morning study, numbering (30). A student. The researcher also adopted an experimental design (two groups) with pre- and post-tests. Achieving the current research procedures required building an educational program based on the art of doodles. For the purpose of measuring the effect